Message from the Chief Editor: JTET June 2019 - Editor, Chief (Journal of Technical Education and Training, 2019)
Message from the Chief Editor: JTET June 2019 Welcome to Vol. 11, Issue 2 of JTET. Nine articles from Bangladesh, Indonesia, Iran, Malaysia, Nigeria and Rwanda on various topics including skills development, training of trainers, competence assessment, employability and lifelong learning are here presented. In the 1st paper, Saleh, Rasul and Mohd Afandi lamented on the need for further guidance in teaching design skills to teacher trainees to which they propose a solution in the form of a framework that can be used to teach a CAD based product design course. In the 2nd paper, Khabiri and Akhavan Bahabadi share their experience in teaching a laboratory course that aim to develop occupational specific skills on civil engineering pavement works. They compare data obtained from teachers, students and industries to gain an insight on the adequacy of existing training on pavement works. They also compare the efficacy between an active laboratory teaching approach and their current approach to gather empirical data for decision making on future laboratory teaching and learning practices. In the 3rd paper, which focuses on problem solving skills, the authors Omar et al. discuss how three elements of mind, the cognitive, affective and conative elements interact to influence problem solving skills among engineering students. Findings obtained from Omar et al. can help teachers in making appropriate pedagogical decisions for promoting problem solving skills. Making good pedagogical decisions however, depends on having adequate occupational specific knowledge and skills. TVET teachers must also have the occupational specific knowledge and skills to be effective in their teaching. Thus, there is a need to train TVET teachers on occupational skills to ensure their teaching competence as reported by Kim, Shin, Woo, and Kim in the 4th paper. Competent teachers are expected to be effective at developing students’ occupational competence which can be gauged using valid competency based assessment (CBA) tools. In the 5th paper, Ana, et al. share validation data on such an assessment instrument which they field tested in Indonesia and Laos. The validated CBA tool can be of future use by teachers to assess competency of interns. Besides teachers, employers can also provide assessment data on interns as shown in the 6th paper. In the 6th paper which is authored by Ghazalan et al. the generic skills of engineering graduates is determined using employers’ assessment. In brief, institutions and industry can collaborate by undertaking joint responsibility in providing assessment data for the betterment of TVET provisions. Upon graduations, TVET graduates are expected to be successfully employed and thus, ensuring graduate employment is of great concern to all TVET providers. In the 7th paper, Afrad and Barau share on the challenges that one developing country i.e., Bangladesh is facing in providing educational programmes that meet industry needs. Afrad and Barau also report on the efforts that they undertake to close the identified curriculum-industry gaps which could be useful to other TVET providers. Further on, focussing on employability potential specifically, Abdul Karim and Maat in the 8th paper, propose a guiding model for promoting employability potential among engineering technology students. This model could alert training providers on aspects to be emphasized in the preparation process for graduate employability. While securing employment for TVET graduates is well and good, reducing disparity in the participation rate of males and females in the job market is equally important. Current lower participation rate of female workers in technical related professions has been of concern and the need to have a better understanding towards factors that contribute to such a phenomenon is high. Focusing specifically on this issue, the last paper by Tahmina, Mohamad and Dahri discuss their findings on the influence of work-place and family support factor on the retention rate of female workers using female workers from a TVET higher learning institution in Malaysia as examples. Differences are found in the influence between work-place support and family support which necessitate further investigations for better planning towards recruitment and retention of female workers. With the last paper, I would like to end this message by expressing my gratitude to everyone involved in making this publication possible; thank you to contributing authors, reviewers and editors. Thank you also to all our readers for your continuing interest in this journal. Professor Dr. Maizam Alias Chief Editor